Systemic Social Innovation: Co-Creating a Future Where Humans and all Life Thrive - Fisk, Raymond; Fuessel, Angie; Laszlo, Christopher; Struebi, Patrick; Valera, Alessandro; Weiss, Carey (Humanistic Management Journal, 2019)
Society is at a crossroads. Interconnected systems, radical transparency, and rapidly increasing sophistication in skills, communications, and technologies provide a unique context for fostering social innovation at a planetary scale. We argue that unprecedented rates of systemic social change are possible for co-creating a future where humans and all life can thrive. Yet, this requires innovation in the conceptions, practice, teaching, and researching of social innovation itself to reimagine what it is and can be. As a multidisciplinary group of academics, practitioners, and educators, we integrate our perspectives on social innovation and humanistic management to suggest the notion of systemic social innovation. We introduce the concept of “transformative collaboration” as central to facilitating systemic social innovation and propose a multilevel model for accelerating systems change. We then develop an integrated framework for conceptualizing systemic social innovation. Four levels of social impact are identified, and these levels are bracketed with a call for transforming individual consciousness at the micro level and new collective mindsets at the macro level. Blooom is presented as a case study to illustrate transformative collaboration, demonstrate the role of mindset shift in practice, and introduce four key ingredients to systemic social innovation. Finally, a call to action is issued for social innovation practice, teaching, and research. Most importantly, we seek to inspire and accelerate systemic social innovation that enables the flourishing of every human being and all life on earth.
Number: 2
Keywords: Co-création; Collaboration transformatrice; Innovation sociale; Innovation sociale systémique; Réservé UdeM; Systemic social innovation; Technologie